BERKILAU DI DUNIA BISNIS : LITERASI, TEKNOLOGI DAN AKUNTANSI MEMBENTUK KINERJA UMKM - Alievya, Rizki Nur; Litdia, Litdia (Taksasila Edukasi Insani, 2024)
This study aims to determine and analyze the effect of Financial Literacy, Information Technology, and Accounting Information Systems. The theory used is TAM (Technology Acceptance Model) theory. Reespondence totaled 73 MSME players consisting of 6 Malls domiciled in South Tangerang. The research method used is quantitative method, with the sampling technique used is sampling. This research data testing was processed using SMART_PLS. The result Financial Literacy and Accounting Information System have a positive and significant effect on SME Financial Perforrmance, Information Technology has a positive and insignificant effect on SME Financial Performance.